Lonchocarpus cultratus, a Brazilian savanna tree, endures high soil Pb levels - Oliveira, Dayane Gomes (2021)
Industrial revolution markedly increased the environmental contamination by different pollutants, which include the metal lead (Pb). The phytoremediation potential of native species from tropical regions is little known, especially for woody plants. The present study aimed to evaluate the performance of Lonchocarpus cultratus (Fabaceae), a tree species from the Brazilian savanna, grown in soil that was artificially contaminated with increasing Pb concentrations (control and 4 Pb treatments, 56, 120, 180, and 292 mg kg−1) for 6 months. The biomass of L. cultratus was not depressed by exposure to Pb, despite the high accumulation of this metal (up to 7421.23 μg plant−1), indicating a high plant tolerance to this trace metal. Lead was mainly accumulated in roots (from 67 to 99%), suggesting that the low root-to-shoot Pb translocation is a plant strategy to avoid Pb-induced damages in photosynthetic tissues. Accordingly, the content of chlorophylls a and b was maintained at similar levels between Pb-treated and control plants. Moreover, increments in leaf area were noticed in Pb-treated plants in comparison to the control plants (on average, 24.7%). In addition, root length was boosted in plants under Pb exposure (22.6–66.7%). In conclusion, L. cultratus is able to endure the exposure to high Pb concentrations in soil, being a potential plant species to be used for Pb phytostabilization in metal-contaminated soils in tropical regions.